Impact of Perceived Influence, Virtual Interactivity on Consumer Purchase Intentions Through the Path of Brand Image and Brand Expected Value - Jia, Xinzhong; Alvi, Abdul Khaliq; Nadeem, Muhammad Aamir; Akhtar, Nadeem; Zaman, Hafiz Muhammad Fakhar (Frontiers in Psychology, 2022)
Many researchers are currently showing interest in researching consumers who are purchasing the products with the help of new tools, and new kinds of markets are emerging rapidly. M-Commerce is a prevalent mode of marketing and is famous among young people of Pakistan. M-Commerce is sales done with the help of mobile ads. Current research is planned to check the status of consumer purchase intentions using perceived influence, virtual interactivity, brand image, and brand expected value among customers who purchase their products with the help of m-commerce. Data was collected from customers who were engaged in buying with the help of M-Commerce by using the convenience sampling technique and 227 complete questionnaires were used in final analysis. This research examines the direct impact of perceived influence, virtual interactivity, brand image, and brand expected value on purchase intentions and finds the indirect effect of brand image and brand expected value on the relationships of perceived influence and virtual interactivity with purchase intentions. Results indicate that all the hypotheses of direct relationships are accepted except the hypothesis for the relation of virtual interactivity with consumer purchase intentions. Virtual interactivity has an insignificant positive impact on consumer purchase intentions. Brand expected value has a strong positive effect on consumer purchase intentions among all. The current study proposed four sequential mediational hypotheses. All five sequential mediational hypotheses are accepted.